Allometry and morphophysiology of papaya seedlings in a substrate with polymer under irrigation with saline water - Nascimento Neto, Expedito Cavalcante; Bezerra, Francisco Thiago Coelho; Bezerra, Marlene Alexandrina Ferreira; Pereira, Walter Esfrain; Cavalcante, Lourival Ferreira; Oliveira, Flaviano Fernandes de (Comunicata Scientiae, 2020)
The availability and quality of the irrigation water are among the limitations for the development of agriculture in the semiarid. Aiming at gathering information on these limitations, this work aimed to evaluate the association between a water-absorbing polymer and water salinity in irrigation frequencies, as well as container volumes on the allometric and morphophysiological indices of seedlings of the papaya (Carica papaya) cultivar ‘Sunrise Solo’. The treatments were obtained from the combination between the water-absorbing polymer (0.0; 0.2; 0.6; 1.0, and; 1.2 g dm-3), the electrical conductivity of the irrigation water (0.3; 1.1; 2.7; 4.3, and; 5.0 dS m-1), and irrigation frequencies (daily and alternate), plus two additional treatments (0.75 and 1.30 dm3) to study the effects of the container volume, distributed in a randomized block design. At 55 days after sowing, the following characteristics were evaluated: ratio between stem height and diameter; ratio between shoot and root dry matter; root density; leaf blade area; ratio between total leaf area and root dry mass; specific leaf area; leaf area ratio; leaf mass ratio; and Dickson quality index. The allometric and morphophysiological indices were damaged by the increase of water electrical conductivity and favored by the application of the polymer and a higher irrigation frequency. In the production of papaya seedlings, a daily irrigation frequency must be prioritized, using containers of 0.75 or 1.30 dm-3, water with electrical conductivity up to 2.6 and 1.9 dS m-1 when irrigated daily or in alternate days, respectively, and 0.6 g dm-3 of polymer.